Psychometric validation of an instrument to evaluate the context of quality improvement and accreditation of hospitals - Mario Zapata-Vanegas; Pedro J Saturno Hernández (Salud Pública de México, 2018)
Objective. To adapt and validate an instrument to measure the context factors which favor quality improvement initiatives and accreditation of hospitals. Materials and methods. The model and questionnaire Model for Understanding Success in Quality (MUSIQ) is adapted and validated for application in Spanish-speaking countries and its specific use in hospital accreditation projects. The theoretical construct of its dimensions is assessed by confirmatory factor analysis (Bartlett test and Kaiser-Meyer-Olkim index) and internal consistency (Cronbach’s a), in a study carried out in a sample of 54 hospitals of medium and high complexity in Colombia. Results. Instrument with four dimensions of context (environment, macrosystem, microsystem, quality team), composed of 23 elements that are measured through 35 variables. Factor analysis showed statistical significance and adequacy of the dimensions, which had also good internal consistency. Conclusion. Adapted instrument with usefulness for measurement of context elements that can promote initiatives of improvement and accreditation in hospitals.